Scutellaria baicalensis extract and baicalein inhibit replication of SARS-CoV-2 and its 3C-like protease in vitro. (1st January 2021) - Liu, Hongbo; Ye, Fei; Sun, Qi; Liang, Hao; Li, Chunmei; Li, Siyang; Lu, Roujian; Huang, Baoying; Tan, Wenjie; Lai, Luhua
Abstract: COVID-19 has become a global pandemic and there is an urgent call for developing drugs against the virus (SARS-CoV-2). The 3C-like protease (3CL pro ) of SARS-CoV-2 is a preferred target for broad spectrum anti-coronavirus drug discovery. We studied the anti-SARS-CoV-2 activity of S. baicalensis and its ingredients. We found that the ethanol extract of S. baicalensis and its major component, baicalein, inhibit SARS-CoV-2 3CL pro activity in vitro with IC50 's of 8.52 µg/ml and 0.39 µM, respectively. Both of them inhibit the replication of SARS-CoV-2 in Vero cells with EC50 's of 0.74 µg/ml and 2.9 µM, respectively. While baicalein is mainly active at the viral post-entry stage, the ethanol extract also inhibits viral entry. We further identified four baicalein analogues from other herbs that inhibit SARS-CoV-2 3CL pro activity at µM concentration. All the active compounds and the S. baicalensis extract also inhibit the SARS-CoV 3CL pro, demonstrating their potential as broad-spectrum anti-coronavirus drugs.